Z‐scheme 3 D g‐C3N4/TiO2−x Heterojunctions with High Photocatalytic Efficiency. Issue 36 (23rd September 2020) - Li, Zhenxing; Ge, Kai; Yang, Kai; Wang, Shuang; Li, Xuehan; He, Jiahui; Fu, Congcong; Ye, Jin; Zhang, Yue; Yang, Yongfang
Abstract: The 3D network structure composed of g‐C3 N4 nanorods was prepared via treatment of bulk g‐C3 N4 with hot HNO3 followed by adjustment the pH and lyophilization. Then the 3D g‐C3 N4 /TiO2−x heterojunctions with a strong interface was constructed via loading TiO2−x nanoparticles onto the 3D g‐C3 N4 networks under hydrothermal conditions. The structure and morphology of the 3D g‐C3 N4 /TiO2−x heterojunctions was characterized by infrared spectrum (FTIR), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM) and field emission transmission electron microscope (TEM). The photo‐degradation rate of Doxycycline HCl for 3D g‐C3 N4 /TiO2−x heterojunction is about 4 times of that original bulk‐C3 N4 and 2.75 times of 3D g‐C3 N4 . The improved photocatalytic efficiency is attributed to 3D g‐C3 N4 networks, which provides the more transfer channel to accelerate the electron transportation and the strong heterointerface between g‐C3 N4 and TiO2−x which promotes the separation of the electron‐holes. Besides, more adsorption capacity of the pollutant onto the 3D g‐C3 N4 /TiO2−x also contributed to this high efficiency. Abstract : Herein, the 3D g‐C3 N4 /TiO2−x composite material was successfully prepared by the hydrothermal synthesis method. The 3D g‐C3 N4 /TiO2−x material possessed the highest photocatalytic efficiency towards degradation of doxycycline hydrochloride due to the formation of heterojunction and the synergistic effect of ESR.